Enrichment of Acanthamoeba Culture Medium Using TYIS 33 Medium: a Step toward a Successful Axenic Cultivation - Niyyti, Maryam; Dodangeh, Samira (Novelty in Biomedicine, 2015)
Background: Acanthamoeba-related disease have a poor prognosis according to many previous studies. Thus researches regarding biochemical and molecular aspects of this organism are a high priority. To this end achieving high amount of amoebae in culture is the first step for such studies. The main aim of the present research was to address the usage of TYI-S-33 (Tripticase, Yeast extract, iron-serum) medium as an enrichment component for achieving high and fast growth of trophozoites in agar culture medium within 24 hours. Materials and Methods: Overall, 10 Acanthamoeba strains were cultured, cloned and genotyped and the cultures were then enriched with addition of TYI-S-33 medium. Amoebae growth was then monitored daily. Ten plates also were used without addition of TYI-S-33 medium. Results: The result of the present research revealed that addition of TYI-S-33 medium is a promising approach for obtaining 100% trophozoites within 24 hours of culture. Conclusion: To the best of our knowledge this is the first report of successful achieving high amount of trophozoites within short time that able researchers to arrange molecular and biochemical assays